Liver dysfunction in patients bitten by Crotalus Durissus terrificus (Laurenti, 1768) snakes in Botucatu (State of São Paulo, Brazil). - Barraviera, B. [UNESP]; Coelho, K. Y. [UNESP]; Curi, P. R. [UNESP]; Meira, D. A. [UNESP] (My University, 1995)
Thirty-two patients bitten by venomous snakes sixteen by Bothrops spp. and sixteen by Crotalus durissus terrificus were studied. The group comprised thirty males and two females, aged eight to sixty-three years (mean 33 +/- 15). Bromsulphalein tests were increased in the majority of patients bitten by Crotalus durissus terrificus. The correlation coefficient of Spearman was positive between bromsulphalein tests and alanine aminotransferase levels, and between alanine aminotransferase and aspartate aminotransferase levels only in the Crotalus group. The only patient who died was bitten by Crotalus durissus terrificus and showed hydropic degeneration and mitochondrial injury in the liver. It was concluded that the hepatic damage might have been caused by at least two possible mechanisms: venom effect on liver mitochondria and cytokine effects on hepatocyte, specially interleukin-6.